2004
DOI: 10.1038/sj.ejhg.5201144
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heavy neurofilament subunit gene polymorphism in Russian patients with sporadic motor neuron disease (MND)

Abstract: Motor neuron disease (MND) results in the selective degeneration of motor neurons in the cerebral cortex, brain stem and spinal cord. The most common form of MND is amyotrophic lateral sclerosis (ALS). MND is complex and many genetic systems may be involved in the pathogenesis of this disease. Pathological and animal studies implicate neurofilament involvement in MND. The heavy subunit (NEFH) tail domain contains a repeated motif. In humans, there are two common variants: the 45 motif repeats long allele (L) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Mouse models with overexpression of neurofilaments subunits have a motor neuropathy resembling ALS [20]. Rare mutations in the peripherin and in the KSP repeats motifs have been reported [1, 8], and a latter study showed that a short allele of the NEFH tail was associated with ALS [30]. Other studies found no mutations of NEFH in ALS [9, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models with overexpression of neurofilaments subunits have a motor neuropathy resembling ALS [20]. Rare mutations in the peripherin and in the KSP repeats motifs have been reported [1, 8], and a latter study showed that a short allele of the NEFH tail was associated with ALS [30]. Other studies found no mutations of NEFH in ALS [9, 28].…”
Section: Discussionmentioning
confidence: 99%
“…12 Neurofilaments are type IV intermediate filaments that are the main structural component of the cytoskeleton in mature neurons 13 determining axon caliber and conductivity for proper neuronal function. 14,15 Neurofilaments have been implicated in the pathology of neurological diseases, [16][17][18] but recent data also point to a role in the pathology of cancer. [19][20][21] For example, NEFL and NEFM are both located within the 8p21 chromosome region and LOH of this region has been described in several cancers including breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In humans there are two common polymorphic variants of 44 (short) or 45 (long) repeats. Homozygosity for the short repeat allele is associated with Russian sporadic motor neuron disease patients (Skvortsova et al, 2004). Deletions and insertions in the KSP repeats of NEFH were detected in ALS patients (Al-Chalabi et al, 1999;Figlewicz et al, 1994;Tomkins et al, 1998).…”
Section: Neurofilaments (Nefl Nefm Nefh)mentioning
confidence: 99%